2014
DOI: 10.4238/2014.february.21.3
|View full text |Cite
|
Sign up to set email alerts
|

Selection of DNA barcoding loci for Nepeta deflersiana Schweinf. ex Hedge from chloroplast and nuclear DNA genomes

Abstract: ABSTRACT. Molecular markers, mainly DNA-based are potential tools for DNA barcoding and phylogenetic study. The plant species belonging to the Nepeta genus have important medicinal value because of the presence of nepetalactones, and they have been used to treat human diseases. We amplified nuclear and chloroplast gene loci to develop a DNA barcode and phylogenetic study of Nepeta deflersiana. Among the studied loci, psbA-trnH and rps16 showed less identity within the genus than the other loci using the Basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Recently, various studies have shown that DNA markers are highly effective in identifying medicinal plants at genus and species levels. Thus, the ITS marker used in this study showed the phylogenetic relationship of E. macrochaetus to the other species of Echinops, and a higher capacity of this marker in terms of phylogenetic reconstruction has been proven in other research studies [41][42][43].…”
Section: Discussionmentioning
confidence: 63%
“…Recently, various studies have shown that DNA markers are highly effective in identifying medicinal plants at genus and species levels. Thus, the ITS marker used in this study showed the phylogenetic relationship of E. macrochaetus to the other species of Echinops, and a higher capacity of this marker in terms of phylogenetic reconstruction has been proven in other research studies [41][42][43].…”
Section: Discussionmentioning
confidence: 63%
“…Results revealed the proximity and maximal identity of Resedae with 100% bootstrap support and nested within the clade. Al-Qurainy et al (2013, 2014a,b) analyzed five species of rare and endangered plants from Saudi Arabia. Al-Qurainy et al (2014a,b) evaluated medicinal plants Nepeta deflersiana and Plectranthus asirensi using DNA barcoding.…”
Section: Plant Dna Barcoding: An Emerging Approachmentioning
confidence: 99%
“…Al-Qurainy et al (2013, 2014a,b) analyzed five species of rare and endangered plants from Saudi Arabia. Al-Qurainy et al (2014a,b) evaluated medicinal plants Nepeta deflersiana and Plectranthus asirensi using DNA barcoding. In their study, they used various markers (Table 1), among which ITS was suggested for rare and endangered plant species, including P. asirensi (with the exception of N. deflersiana ).…”
Section: Plant Dna Barcoding: An Emerging Approachmentioning
confidence: 99%
“…Alaklabi et al (2014) used the rbcL gene to identify the endangered tree Diospyros mespiliformis (Ebenaceae). Furthermore, Al-Qurainy et al (2014) used the nuclear gene ITS for identification of Nepeta deflersiana (Lamiaceae). Ali et al (2015) used ITS1 and ITS4 primers in DNA barcodes to study the system of the genus Echinops (Asteraceae).…”
Section: Introductionmentioning
confidence: 99%